2020
DOI: 10.3390/ma13183980
|View full text |Cite
|
Sign up to set email alerts
|

Recent Trends in Three-Dimensional Bioinks Based on Alginate for Biomedical Applications

Abstract: Three-dimensional (3D) bioprinting is an appealing and revolutionary manufacturing approach for the accurate placement of biologics, such as living cells and extracellular matrix (ECM) components, in the form of a 3D hierarchical structure to fabricate synthetic multicellular tissues. Many synthetic and natural polymers are applied as cell printing bioinks. One of them, alginate (Alg), is an inexpensive biomaterial that is among the most examined hydrogel materials intended for vascular, cartilage, and bone ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(43 citation statements)
references
References 177 publications
(244 reference statements)
0
38
0
1
Order By: Relevance
“…Three dimensional (3D) bioprinting is an evolving adaptive manufacturing technique that offers the development of wound treatments that can deal with the issues presented by traditional wound dressings (i.e., need for frequent dressing change, adherence to wound tissue making dressing changes painful) [ 126 ]. The bioprinting process integrates cell-laden hydrogels, also called bioinks, together with motorized systems to create complex structures that can be catered precisely to the patient or situation in question [ 79 , 80 , 126 , 127 , 128 ]. In 2009, a 3D-printed human skin construct incorporating collagen I together with fibroblasts and keratinocytes was the first successful attempt at creating a skin implant.…”
Section: Collagen Formats and Applications In Wound Healingmentioning
confidence: 99%
“…Three dimensional (3D) bioprinting is an evolving adaptive manufacturing technique that offers the development of wound treatments that can deal with the issues presented by traditional wound dressings (i.e., need for frequent dressing change, adherence to wound tissue making dressing changes painful) [ 126 ]. The bioprinting process integrates cell-laden hydrogels, also called bioinks, together with motorized systems to create complex structures that can be catered precisely to the patient or situation in question [ 79 , 80 , 126 , 127 , 128 ]. In 2009, a 3D-printed human skin construct incorporating collagen I together with fibroblasts and keratinocytes was the first successful attempt at creating a skin implant.…”
Section: Collagen Formats and Applications In Wound Healingmentioning
confidence: 99%
“…However, a study on alginate bioinks reported to have high viscosity, and thus will induce shear-thinning properties during printability by using extrusion-based bioprinting [ 73 ]. Therefore, the printability quality of alginate bioinks can be achieved using a suitable nozzle size and adjust the viscosity based on a suitable concentration for the printing process [ 44 ].…”
Section: Strategies To Achieve Optimal Printability Quality For 3dmentioning
confidence: 99%
“…Previous studies reported that the use of natural-based bioinks gives an excellent scaffold porosity product. A study of alginate scaffold porosity revealed that the alginate scaffold’s pore sizes are in various sizes ranging from 5–200 nm according to different concentrations [ 44 ].…”
Section: Strategies To Achieve Optimal Printability Quality For 3dmentioning
confidence: 99%
“…Biyouyumlu, düşük maliyetli ve farklı basım tekniklerine uygun olması önemli özelliklerindendir. Lineer bir kopolimer olan aljinat, β-(1-4)-D-mannuronik asit (M) ve α-(1-4)-L-guluronik asit (G) monomerlerinden oluşur [16]. Aljinatın yapısı elde edildiği bölgeye göre değişir.…”
Section: Aljinatunclassified